Direito e redução das desigualdades entre as regiões brasileiras : um estudo sobre a I Política Nacional de Desenvolvimento Regional (PNDR) - Silva, Felipe Felix e (2017)
The object of this thesis will be a legal analysis of the I National Policy on Regional Development (NPRD), institutionalized by the Decree n° 6.047/2007. The structure will be based on an analitical methodology on Right and Public Policies which, when considering a public policy as a paradigm, demands an evaluation through the of its elements by segregating its elements, that are, metaphysical principles, general hypothesis, methodologies and specific instruments. Law must be, then, a fundamental element of action. Regarding the approach of the problem, it is followed, predominantly, a qualitative method; however it is also held quantitative data collection so as to confirm or adjust the hypothesis rised. A difficulty while producing this dissertation concerns the “pulverization” of actions, initiatives, projects, institutions and budgetary information referring to the object. Therefore, the examples given and the data collected to investigate the hypothesis were focused on Northeast Region. This way, it is intended to be sensitive to the local without disconsidering the national. The introduction explicits object, objective, hypothesis and methods, as well as highlights theoretical-descriptive matters which are necessary for the dissertation to be started, properly, confronting the theme. All four elements composing NPRD are segmented on the two sections following. At first, are presented the metaphysical principles, explicit and implicit to the normative text, and the hypothesis enfolded; the next one considers specific instruments for funding the NPRD and the methodologies both the existing and required ones. The purpose of this division is to put apart the most general and mandatory elements (principles and hypotheses) from the others, more concrete and operative (instruments and methogologues). Last section aims to presenting one more component for a regional field of study, that is, the federalist environment, because, to the extent that there is no explicit territorial concern, based on regional solidarity, inequality feeds itself back. After this aproximation, the thesis can be concluded by indicating a severe fragmentation of the NPRD I, mostly where is concerned the absence of an integrative methodology normatively inscribed.